Roles for Maine’s Physicians in the Climate Crisis - Carlson, Gail; Andersen, Megan (Maine Policy Review, 2024)
Physicians have important roles to play in the climate crisis because they deal with the health impacts of climate change. We surveyed physicians in Maine about climate change and health, and of the 108 respondents, 84 (78 percent) believe that climate change poses a threat to the health of their patients, particularly for asthma, vector-borne diseases, heat-related illnesses, chronic obstructive pulmonary disease, and mental health problems. Most reported that these conditions are becoming more prevalent, and they identified children, older adults, and patients with chronic health conditions as those most at risk. Despite this awareness, most respondents did not discuss climate change as a health determinant with their patients, although they identified communicating with patients and the public as a role for physicians.